2006
DOI: 10.1080/02678290600617462
|View full text |Cite
|
Sign up to set email alerts
|

Phase transition behaviour of novel Y‐shaped liquid crystal oligomers

Abstract: We have designed novel liquid crystal oligomers in which three mesogenic units are connected via 3,5-dihydroxybenzoic acid. 4-Cyanobiphenyl-49-yl 3,5-bis{6-[4-(5-octylpyrimidin-2-yl)phenyloxy]hexyloxy}benzoate and 4-(5-octylpyrimidine-2-yl)phenyl 3,5-bis{6-[4-(5-octylpyrimidine-2-yl)phenyloxy]hexyloxy}benzoate have been prepared, and their physical properties investigated by optical microscopy and differential scanning calorimetry. The Yshaped liquid crystal oligomers were found to show a direct phase transiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…At high-field, the twelve methylene protons of the C 8 H 16 spacer give rise to two sets of multiplets at d=1.44-1.88 ppm. A triplet at d=4.07 ppm assignable to four methoxy protons, on the other hand, is similar to the absorption reported for 5-octylpyrimidine-2-yl oligomers [17]. Although the overall structure is non-symmetric due to two different mesogenic groups, the appearance of only one triplet owing to the two pairs of methoxy protons indicates the presence of symmetry in the flexible spacer.…”
Section: Spectroscopic Resultssupporting
confidence: 62%
“…At high-field, the twelve methylene protons of the C 8 H 16 spacer give rise to two sets of multiplets at d=1.44-1.88 ppm. A triplet at d=4.07 ppm assignable to four methoxy protons, on the other hand, is similar to the absorption reported for 5-octylpyrimidine-2-yl oligomers [17]. Although the overall structure is non-symmetric due to two different mesogenic groups, the appearance of only one triplet owing to the two pairs of methoxy protons indicates the presence of symmetry in the flexible spacer.…”
Section: Spectroscopic Resultssupporting
confidence: 62%
“…Recently Yoshizawa et al [15] have reported the synthesis and physical properties of novel S-shaped LC oligomers in which two U-shaped mesogenic molecules are connected. Yoshizawa et al [16] have also reported novel Y-shaped LC oligomers in which three mesogenic units are connected by 3,5-dihydroxybenzoic acid. Y-shaped LC oligomers are found to exhibit only an anticlinic SmC anti (SmC) phase.…”
Section: Introductionmentioning
confidence: 95%
“…We have reported liquid crystal oligomers in which cyanobiphenyl and phenylpyrimidine moieties are connected via a flexible spacer [18][19][20], 1,3-dihydroxybenzene [21], 3,4-dihydroxybenzoic acid [22][23][24] or 3,5-dihydroxybenzoic acid [25], as shown in Figure 1. Intermolecular interactions between such mesogenic moieties were found to have significant effects on the molecular assemblies in the liquid-crystalline phases: (i) antiparallel interactions between cyanobiphenyl moieties promote the formation of N and SmA phases, (ii) interactions between phenylpyrimidine moieties were found to stabilize smectic phase [26], and (iii) interactions between cyanobiphenyl and phenylpyrimidine moieties are known to induce an SmA phase [27].…”
Section: Introductionmentioning
confidence: 98%